Answer:
I think its aas
Step-by-step explanation:
Answer:
-4, -24
Step-by-step explanation:
The location of Z is either +10 or -10 units away from Y, since YZ = 10. Then Z could be located at either -4 or -24.
Answer:
1st: 3*root6 + 5
2nd: 35*root2 + 115
3rd: 24*root2 - 20*root6 + 15*root3 - 18
4th: 17*root6 - 38
5th: 13*root10 - 42
Step-by-step explanation:
To simplify these expressions we need to use the distributive property:
(a + b) * (c + d) = ac + ad + bc + bd
So simplifying each expression, we have:
1st.
(2 root 2 + root 3 ) ( 2 root 3 - root 2)
= 4*root6 - 2*2 + 2*3 - root6
= 3*root6 - 4 + 9
= 3*root6 + 5
2nd.
(root 5 + 2 root 10) (3 root 5 + root 10)
= 3 * 5 + root50 + 6*root50 + 2*10
= 15 + 5*root2 + 30*root2 + 100
= 35*root2 + 115
3rd.
(4 root 6 - 3 root 3) (2 root 3 - 5)
= 8*root18 - 20*root6 - 6*3 + 15root3
= 24*root2 - 20*root6 + 15*root3 - 18
4rd.
(6 root 3 - 5 root 2 ) (2 root 2 - root 3)
= 12*root6 - 6*3 - 10*2 + 5*root6
= 17*root6 - 18 - 20
= 17*root6 - 38
5th.
(root 10 - 3 ) ( 4 - 3 root 10)
= 4*root10 - 3*10 - 12 + 9*root10
= 13*root10 - 30 - 12
= 13*root10 - 42
Answer:
y= -6/5x -3
Step-by-step explanation:
So for now lets bring it into mx + b format
Subtract 6x from both sides to isolate y which is also called subtraction property of equality.
so 5y = -6x -15
Now you divide both sides by 5 which is called division property of equality.
You now have y = -6/5x - 3
y= -6/5x -3 is the slope intercept form of the standard form equation of 6x + 5y = -15.
Hope this helps!